Energy Drinks and the Neurophysiological Impact of Caffeine - Bagwath Persad, Leeana (Frontiers in Neuroscience, 2011)
Caffeine is the most widely used psychoactive stimulant with prevalent use across all age groups. It is a naturally occurring substance found in the coffee bean, tea leaf, the kola nut, cocoa bean. Recently there has been an increase in energy drink consumption leading to caffeine abuse, with aggressive marketing and poor awareness on the consequences of high caffeine use. With caffeine consumption being so common, it is vital to know the impact caffeine has on the body, as its effects can influence cardio-respiratory, endocrine and perhaps most importantly neurological systems. Detrimental effects have being described especially since an over consumption of caffeine has being noted. This review focuses on the neurophysiological impact of caffeine and its biochemical pathways in the human body.